1999
DOI: 10.1021/ac980946f
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-4-hydrazino-7-nitrobenzofurazan as a New Reagent for Air Monitoring of Aldehydes and Ketones

Abstract: The synthesis of N-methyl-4-hydrazino-7-nitrobenzofurazan (MNBDH) and its application as a new reagent for the determination of aldehydes and ketones are described. MNBDH reacts with carbonyl compounds in acidic media to the corresponding MNBD-hydrazones. In contrast to the established reagent 2,4-dinitrophenylhydrazine (DNPH), MNBDH is oxidized by both ozone and nitrogen dioxide quantitatively to only one product, N-methyl-4-amino-7-nitrobenzofurazan (MNBDA). This can easily be separated from the hydrazones o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 17 publications
(28 reference statements)
2
41
0
1
Order By: Relevance
“…In our study, a single and intense fragment ion at m/z 151 was observed in the product ion spectra, which might be favorable for the detection in MRM. Although the attained detection limits in this study were comparable to those obtained with cyclohexanediones or a little less sensitive than those obtained with 4-(N,N-dimethylaminosulfonyl)-7-hydrazino-2,1,3-benzoxadiazole (DBD-H) and 4-aminosulfonyl-7-hydrazino-2,1,3-benzoxadiazole (ABD-H) (Uzu et al, 1990) for fluorescent detection, and N-methyl-4-hydrazino-7-nitrobenzofurazan (MNBDH) (Buldt and Karst, 1999) and 4-(N,N-dimethylaminosulfonyl)-7-Nmethylhydrazino-2,1,3-benzoxadiazole (MDBDH) (Jackmann and Karst, 2001) for ultraviolet/visible detection. Hydrazino or methylhydrazino groups were appropriate as the reaction group for aldehydes, since these reagents reacted with aldehydes rapidly under mild conditions.…”
Section: Resultssupporting
confidence: 79%
“…In our study, a single and intense fragment ion at m/z 151 was observed in the product ion spectra, which might be favorable for the detection in MRM. Although the attained detection limits in this study were comparable to those obtained with cyclohexanediones or a little less sensitive than those obtained with 4-(N,N-dimethylaminosulfonyl)-7-hydrazino-2,1,3-benzoxadiazole (DBD-H) and 4-aminosulfonyl-7-hydrazino-2,1,3-benzoxadiazole (ABD-H) (Uzu et al, 1990) for fluorescent detection, and N-methyl-4-hydrazino-7-nitrobenzofurazan (MNBDH) (Buldt and Karst, 1999) and 4-(N,N-dimethylaminosulfonyl)-7-Nmethylhydrazino-2,1,3-benzoxadiazole (MDBDH) (Jackmann and Karst, 2001) for ultraviolet/visible detection. Hydrazino or methylhydrazino groups were appropriate as the reaction group for aldehydes, since these reagents reacted with aldehydes rapidly under mild conditions.…”
Section: Resultssupporting
confidence: 79%
“…560 nm). MNBDH was converted to fluorescent N-methyl-4-amino-7-nitro-2,1,3-benzoxadiazole by the reaction with ozone or nitrogen dioxide (Büldt and Karst, 1999a). The detemination of nitrite using MNBDH was also reported (Büldt and Karst, 1999b).…”
Section: For Carboxylic Acids Nbd-pzmentioning
confidence: 99%
“…To test the reactions with 2, we selected two arylhydrazines (3 and 4) that are commonly used as aldehyde-specific dyes. [12,13] The reactions of aldehydenucleotide 2 with 3 or 4 proceeded at room temperature for approximately 20 hours and gave the corresponding orange (5) or violet (6) hydrazones, which were fully characterized (see the Supporting Information). As the formation of hydrazone in water is inherently a reversible reaction, the yields for the isolated products of 51 and 31 %, respectively, were acceptable and useful.…”
mentioning
confidence: 99%